ПЕЙЗАЖ – ПРОЗАЛЫҚ ШЫҒАРМАЛАРДЫҢ ТИЙКАРҒЫ КОМПОНЕНТИ СЫПАТЫНДА - Бекбергенова, З.У. (SCIENCE and SOCIETY, 2016)
The most part of many literary works is landscape drawings. Especially it is observed in epic works, where detailed description of nature, the time and place of heroes‘ actions are given, the psychology and spirit of the time are revealed. This article shows from scientific-theoretical outlook the analysis of the features of using psychological parallel and contrast images, which are given as a device of plot motivating of the details of nature drawings in the compositional structure of the novels ―The apple of an eye‖ by T.Kaypbergenov, ―Broken people‖ by K.Mambetov. ―The years when river became calm‖ by K.Allambergenov.